HUBUNGAN PENGETAHUAN DAN SIKAP DENGAN TINDAKAN PENCEGAHAN HIV-AIDS PADA SISWA SMK X DI KABUPATEN SUMEDANG - Nuridha Fauziyah; Burdahyat Burdahyat; Muhamad Abdul Had (Poltekkes Kemenkes Aceh, 2023)
HIV/AIDS cases are one of the world's health problems. Today's world's youth live side by side with HIV AIDS. It is reported that every 14 seconds, one teenager is infected with the HIV/AIDS virus. Many teenagers do not have adequate information about sexual health, infections caused by sex and HIV-AIDS. This study aims to determine the relationship between knowledge and attitudes with HIV-AIDS prevention measures in adolescents. This type of research is quantitative research, using a cross sectional approach. The sample in this study were students at SMK X in Sumedang Regency with a total of 92 respondents. The side technique used in this study is simple random sampling. The data analysis used was univariate and bivariate analysis using the Chi-Square test. The results of this study revealed that there is a relationship between knowledge and attitudes with HIV-AIDS prevention measures in SMK X students in Sumedang Regency (p value <0.05). Actions and efforts to prevent HIV/AIDS can be carried out by all adolescents through changing behavior by increasing understanding of knowledge and attitudes towards HIV-AID prevention continuously and continuously supported by internal and external school stakeholders.